A phronesis e os saberes docentes na práxis em educação infantil - Schock, Indaia (2022)
This Dissertation is part of the Research Line “Teaching, knowledge and professional development”, of the Graduate Program in Education - Master's Degree in Education, at the Federal University of Santa Maria (UFSM). In its scope, it develops a theoretical dialogue about the formation and exercise of teaching and the convergences between the concepts of phronesis and the dialectical relationship between action-reflection, allowing contributions to the task of the teacher in Early Childhood Education to emerge in the interaction with very young children ( 1 year and 7 months to 3 years and 11 months) (BRAZIL, 2019). It resulted from bibliographic research, of a qualitative nature, prioritizing references to contextualize childhood and children, in addition to interweaving the theoretical foundations of training, towards the professionalism of educators. The document analysis covered public policies, legislation and regulations, mainly the National Curricular Common Base - BNCC and the National Curricular Reference for Early Childhood Education - RECNEI, which represent social achievements related to Early Childhood Education, with other correlated contributions. The text relates professional development, through the acquisition of practical wisdom in the action-reflection dialectic, understanding the way in which the initial training process occurs and how subsequent educational practices contribute to the reflections of continuing education in praxis. The theoretical dialogue was qualified with authors, such as Aristotle, regarding the concept of phronesis; Paulo Freire (1979, 1987, 1999, 2004, 2015, 2021), especially with regard to the dialogicity necessary for the exercise of praxis in education and Maurice Tardif (2012, 2021), to interrelate knowledge and professionalism, always in dialogues with other authors. In the study of references, procedures and interlocutions, contributions from Hans-Georg Gadamer's Philosophical Hermeneutics (1997) were present to help, both in the understanding of central concepts such as training, education and practical wisdom. contributions and construct stood out as the educator builds and signifies his teaching throughout his existence and how he incorporates these knowledge/doings, from different contexts, to his daily practice, with the proposal that they need a formative process dialogic aimed at the education of very young children, questioning the generalization in training and educational policies. concepts derived from philosophical hermeneutics and modern sciences were appropriated, versed in the challenges of individual applications in current situations, ethically punctuated, and these were reinvented from a new prism, in accordance with contemporary needs. The articulations made it possible to discuss the importance of exercising phronesis, relating it to praxis in Early Childhood Education, with dialogicity and respect for individual issues that are revealed in the exercise of the educators' daily professionality. Finally, the importance of respect for dialogic relationships is considered, with the awareness that Early Childhood Education is composed of relational processes between individualities and the multiple singularities covered in the educational context.